Severe congenital lactic acidosis and hypertrophic cardiomyopathy caused by an intronic variant in NDUFB7. Issue 4 (4th February 2021) - Correia, Sandrina P.; Moedas, Marco F.; Naess, Karin; Bruhn, Helene; Maffezzini, Camilla; Calvo‐Garrido, Javier; Lesko, Nicole; Wibom, Rolf; Schober, Florian A.; Jemt, Anders; Stranneheim, Henrik; Freyer, Christoph; et al.
Abstract: Mutations in structural subunits and assembly factors of complex I of the oxidative phosphorylation system constitute the most common cause of mitochondrial respiratory chain defects. Such mutations can present a wide range of clinical manifestations, varying from mild deficiencies to severe, lethal disorders. We describe a patient presenting intrauterine growth restriction and anemia, which displayed postpartum hypertrophic cardiomyopathy, lactic acidosis, encephalopathy, and a severe complex I defect with fatal outcome. Whole genome sequencing revealed an intronic biallelic mutation in the NDUFB7 gene (c.113‐10C>G) and splicing pattern alterations in NDUFB7 messenger RNA were confirmed by RNA Sequencing. The detected variant resulted in a significant reduction of the NDUFB7 protein and reduced complex I activity. Complementation studies with expression of wild‐type NDUFB7 in patient fibroblasts normalized complex I function. Here we report a case with a primary complex I defect due to a homozygous mutation in an intron region of the NDUFB7 gene. Abstract : A combination of whole genome sequencing, RNAseq, and molecular biology revealed causality for complex I deficiency.